E-commerce Adoption in Rural Areas : Challenges and Opportunities for Inclusive Economic Development (Proceeding of The International Conference on Economics and Business, 2023)
The growth of e-commerce has opened new opportunities for rural economic development. This paper investigates the challenges and benefits of e-commerce adoption in rural areas, focusing on infrastructure gaps, digital literacy, and market access. Case studies from Africa and South Asia provide insights into how e-commerce platforms can bridge economic disparities and promote inclusive growth.